The Epistle to the Hebrews - Cockerill, Gareth Lee. (Grand Rapids, Michigan ; Cambridge, U.K. : William B. Eerdmans Publishing Company, 2012)
This commentary by Gareth Lee Cockerill offers insight into the Epistle to the Hebrews, a well-constructed sermon that encourages its hearers to persevere despite persecution and hardships in light of Christ's unique sufficiency as Savior. Cockerill analyzes the book's rhetorical, chiastic shape and interprets each passage in light of this overarching structure. He also offers a new analysis of the epistle's use of the Old Testament -- continuity and fulfillment rather than continuity and discontinuity -- and shows how this consistent usage is relevant for contemporary biblical interpretation. --from publisher description
Hebrews in its environment. The pastor who wrote Hebrews -- The pastor's sermon -- The pastor's congregation -- The pastor's worldview -- When did the pastor write this sermon? -- The message of Hebrews. The sermon's use of the Old Testament -- The sermon's rhetorically effective structure -- The sermon's abiding message -- The sermon's outline -- A very short history of the disobedient people of God (1:1-4:13). Sinai revisited: God has spoken in the eternal, incarnate, now exalted son (1:1-2:18) -- Tested at Kadesh-Barnea: avoid the congregation of the disobedient (3:1-4:13) -- The son's high priesthood--resource and urgency for perseverance (4:14-10:18). The life of faith and the high priesthood of the son (4:14-5:10) -- Don't be unresponsive but grasp what Christ has provided (5:11-6:20) -- Our high priest's legitimacy and eternity (7:1-10) -- Our high priest's all-sufficient sacrifice: a symphony in three movements (8:1-10:18) -- A history of the faithful people of God from creation to consummation (10:19-12:29). The life of preserving faith and the high priesthood of the son (10:19-39) -- The past history of the people of God until the coming of Jesus (11:1-12:3) -- The present history of the people of God until the consummation (12:4-29) -- Instructions for the life of gratitude and godly fear (13:1-25) -- The community of the faithful and the life of gratitude and godly fear (13:1-6) -- The unbelieving world and the life of gratitude and godly fear (13:7-17) -- A sermon sent as a letter (13:18-25).
Includes bibliographical references (pages xxiv-xlix) and indexes.
Keywords: Bible. -- Commentaries